2022
DOI: 10.1001/jamanetworkopen.2022.31885
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1-Year Health Care Expenditures and Utilization Following Minimally Invasive vs Open Nephrectomy

Abstract: IMPORTANCEGiven the widespread adoption and clinical benefits of minimally invasive surgery approaches (MIS) in partial nephrectomy (PN) and radical nephrectomy (RN), assessment of longterm cost implications is relevant. OBJECTIVE To compare health care utilization and expenditures within 1 year after MIS and open surgery (OS). DESIGN, SETTING, AND PARTICIPANTSThis cohort study was conducted using a US commercial claims database between 2013 and 2018. A total of 5104 patients aged 18 to 64 years who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The cumulative data appears to suggest that cost savings with robotic surgery, and minimally invasive approaches at large, are due to decreased complication rates [ 27 , 29 ] and lower readmission rates, and emergency room presentations [ 27 , 28 ]. In our prior study, we also have found that minimally invasive approaches are associated with lower readmission and hospital outpatient visits, supporting these claims [ 4 ]. In post-hoc analysis to understand impact of surgical approach on post-operative kidney function, we observed that dialysis initiation rate was trending lower for robotic versus laparoscopic partial nephrectomy especially when extending the analysis period until lost to follow up, although not significant (eTable 8 in the supplement).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The cumulative data appears to suggest that cost savings with robotic surgery, and minimally invasive approaches at large, are due to decreased complication rates [ 27 , 29 ] and lower readmission rates, and emergency room presentations [ 27 , 28 ]. In our prior study, we also have found that minimally invasive approaches are associated with lower readmission and hospital outpatient visits, supporting these claims [ 4 ]. In post-hoc analysis to understand impact of surgical approach on post-operative kidney function, we observed that dialysis initiation rate was trending lower for robotic versus laparoscopic partial nephrectomy especially when extending the analysis period until lost to follow up, although not significant (eTable 8 in the supplement).…”
Section: Discussionsupporting
confidence: 67%
“…However, the discordance with the cost of utilization is arguably prohibitive, encouraging a discussion regarding its cost benefits and utility. In a previous study [ 4 ], the comparative long-term cost benefits of minimally invasive surgery, including laparoscopic approach, versus traditional open surgery has been shown. Here, we focus on minimally invasive technologies and further investigate the value of robotic versus laparoscopic renal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity may not have major effects on nephrectomy outcomes in general populations. With use of minimally invasive surgical treatment, length of hospital stay can be reduced resulting in equivalent or lower cost than open surgery ( 57 , 58 ). However, the relationship between obesity, race and ethnicity, socioeconomic challenge, and perioperative outcomes is very complex, and patients from racial and ethnic minority backgrounds and neighborhoods with elevated socioeconomic challenges may be unevenly impacted.…”
Section: Discussionmentioning
confidence: 99%
“… 62 While it is often cited that the lower complication rate and shorter hospital stay offset the high cost of robotic procedures, the data supporting this assertation is variable. 4 , 63 Certain novel robotic systems aim to offer lower cost options; the Revo-i system claims a 42% cost reduction when compared with the da Vinci, 15 while the Avatera’s use of single-use instruments eliminates sterilization costs. 56 The Senhance system allows for incorporation of traditional laparoscopic instruments, which are less costly than robotic instruments, and the system is less expensive to maintain than the da Vinci.…”
Section: Discussionmentioning
confidence: 99%